Circulated echovirus 18 strains in Guangdong Province and worldwide: A novel perspective on genetic diversity and recombination patterns - Zhiyu Li; Xiaohan Yang; Ru Bai; Ping Li; Yanting Qin; Mingyong Luo (Virulence, 2025)
Echovirus 18 (E18) has re-emerged as a global public health concern in recent years because of its association with severe neonatal systemic diseases that pose a risk of high mortality. The lack of effective intervention strategies for E18 infections is largely attributed to limited knowledge regarding molecular epidemiology and recombination patterns. In this study, we obtained seven full-length E18 sequences from infants in Guangdong Province and combined them with representative sequences from GenBank. Using this expanded dataset, we analysed the molecular epidemiological features, genetic characteristics, and recombination patterns of E18. Global statistics reveal a distinct double-peak pattern in the frequency of E18 infections throughout the year in the Northern Hemisphere. All strains isolated from clinical specimens were classified as genotype C2, which has emerged as the predominant circulating strain in Guangdong Province and globally. Several potential recombination events with E30 were identified among these seven strains, particularly in the P2 and P3 non-structural regions. This study offers new insights into the global dissemination, genetic diversity, and phylodynamics of E18, potentially providing valuable information for designing antiviral vaccines and the implementation of sustainable surveillance strategies to enhance virus prevention and control during public health crises.